Komunikasi Politik Di Era Digital: Pengaruh Media Sosial Terhadap Opini Publik - Sjoraida, Diah Fatma (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Garut Regency is a region in West Java that holds simultaneous Regional Head Elections. The number of social media users who are the millennial generation is 402,000. Through political communication carried out by the Regional Head candidate pair, Abdusy Syakur Amin and Putri Karlina, they managed to win the Regional Election with 915,780 voters (65% of the vote), where even though they won by a landslide, this pair's victory was not able to increase the votes of parties who use social media, such as millennials, where the votes of millennials were only achieved by 53% of voters from around 915,780 which is a total of 2,005,168 voters in the DPT. This situation is caused by the political communication carried out in the media by the Regional Head candidate in Garut Regency which is still not effective because there is still a negative campaign attacking the couple Abdusy Syakur Amin and Putri Karlina on social media by the successful team of Helmi Budiman and Yudi Nugraha on social media, so that they do not provide a good example to voters on social media, and often create black campaigns which tend not to make voters' sympathy on social media shift to the couple Abdusy Syakur Amin and Putri Karlina. The aim of this research is to determine and analyze the extent to which social media used for political communication or campaigns can influence positive public opinion towards candidates for Regional Head in Garut Regency. The research method uses quantitative descriptive methods with data collection techniques using observation, questionnaires and literature studies, while data analysis uses data quality tests, classical assumption tests, simple linear regression tests, t tests and coefficient of determination tests. From the results of existing research, it can be concluded that the use of social media in political communication has a positive effect on public opinion.